PENINGKATAN KOMPETENSI PEMANDU WISATA LOKAL WISATA SARIBU GONJONG MELALUI PELATIHAN TEKNIK KEPEMANDUAN - Novra, Eddi; Riyanda, Riko; Sasmira, Sasmira (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
An important component in tourism activities is a tour guide or better known as a tour guide A tour guide is someone whose job is to lead a tour and provide for the needs of tourists. Tour guides must have competence in the form of knowledge, skills and experince as well as behaviors that must be owned, internalized, and mastered by tour guides in develoving profesionalis of good service to vistting tourists. Because it is not only related to serviece but also related to tourist satistification. The purpose of this research is to increase the knowledge of local tour guides about guiding techniques and identify effevtive form of guideng techniques to increase the competence of local tour guides. Becausa it is only related to service but also related to tourist satisfaction. The purpose of this research is to increase the knowledge of local tour guides about guiding techniques and identify effevtive form of guiding techniques to increase the competence of local tour guides. This type of research is qualitative with the action methode wiyg the object of research being local tour guides in sarugo tourism village. The informants for this research were Ninik Mamak, Wali Jorong, ok dawirs, and local tour guides in Sarugo Tourism Village. The result showed that local tour guides in the Saribu Gonjong Tourism village had worked as local tour guides but dis not quality the competence standards and the importace of holding training and inviting competent resource person to improve the competence of local guides.Keyword: improvement of competence, tour guide, tourism village